Geography Teachers’ Views on Effective Geography Teaching - (:unkn) unknown (My University, 2017)
Geography teaching is fulfilled within the frame of a specific curriculum and in order to achieve someacquirements in Turkey. Though there are course books prepared in accordance with the curriculumand activities in order to achieve the acquirements in geography teaching, they are geography teacherswho will coordinate and fulfill the curriculum and achieve the terminal behavior defined as education.A qualitative method has been used in order to examine the teachers’ effectiveness in geographyteaching. In three different types of high school, 19 geography teachers were interviewed using a semistructuredinterview form prepared by the researchers. During the interview, the researchers asked theteachers some questions about their teaching methods, teaching techniques and materials used, skillsprovided, classroom management, and developments made through in-service training. The dataacquired were evaluated through content analysis and some categories were formed. According to thefindings, it is seen that the geography teachers are effective in education and training. According to theresults obtained from the research, it is determined that the geography teachers use the materials,methods and techniques in accordance with the curriculum. In addition, it is seen that they participatein the in-service training in order to develop and maintain the effective teaching.
Keywords: Eğitim, Eğitim Araştırmaları; Coğrafya